DINAMIKA FILOSOFI PEMASARAN: ANALISIS PERUBAHAN DARI PRODUKSI MASSAL KE PEMASARAN SOSIAL - Hidayat, Sarah Nursa’diah; Ramona, Nur Syafira; Rohendi, Acep (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2025)
This study discusses the dynamics of changes in marketing orientation in Indonesia, from a mass production paradigm that focuses on cost efficiency to social marketing that emphasizes human values, ethics, and sustainability. The background of this research stems from the reality that the mass production approach is no longer able to meet the increasingly diverse needs of consumers and often neglects social and environmental aspects. The purpose of this research is to analyze the driving factors, transition mechanisms, and strategic implications of this marketing paradigm shift. This research uses a qualitative approach by examining various relevant literature and research results in Indonesia. The results of the study show that digitalization, the role of influencers, and marketing practices in MSMEs and the public sector strengthen the transition to social marketing. The conclusion of the study confirms that the success of contemporary marketing is not only determined by economic achievements, but also by the social contributions and sustainability that can be created.